Demandas municipais e elaboração do Plano de Saúde da Bahia 2012-2015: controle social e planejamento participativo - Oliveira, Gladys Reis de (2016)
This study consists in the use of the information system called SICARFmunicipal which is a system created by the health secretariat of the State of Bahia to organize the demands of society from the Municipal health conferences, in order to Achievement of the 8a. State Conference of Health occurred in the year 2011. Therefore, the general objective of this study is to analyze the system of registration of the final reports (SICARFmunicipal) as a device articulator of the demands of the municipal health conferences in the year 2011 for actions of planning the policy of primary care of the state of Bahia. The specific objectives are: to describe the process of preparation of the SICARFmunicipal and the use of this during the organization of the 8a. State Health Conference of Bahia; Analyze how the technical team of the State Secretariat of Health (SESAB) appropriated the proposals from SICARFmunicipal to construct the state health plan 2012-2015. The methodological approach selected was the qualitative one whose result consisted in the production of two scientific articles whose selected method was the case study and documentary analysis respectively. The first scientific article seeks to describe the process of conception and functioning of the SICARFmunicipal and its contributions to the organization of the 8th. State Health Conference. The second scientific article portrays the analysis of appropriation of the demands of health conferences for the elaboration of the state Health plan 2012-2015, from the SICARFmunicipal, that is, to what extent this process was developed. The analyses showed that the company's demands were incorporated for the purposes of planning actions in the state health plan 2012-2015, representing a breakthrough for the participatory management movement. In addition, the SICARFmunicipal was considered as a strategy of organizing and preparatory support of the state health conference that transparently recorded the social demands. Describing its process of elaboration and execution, confirmed that it was participative, and highlighting its importance for the expansion and development of future modes of organization of the demands by the state, among the various forms of legitimate spaces of listening Social.